Postoperative Outcome of Laparoscopic Appendicectomy- A Study of 100 Cases (Northern International Medical College Journal, 2022)
Background : An elegant, reliable procedure that can be easily performed is laparoscopic appendicectomy (LA). In patients with undiagnosed abdominal pain requiring more diagnostic investigations, as well as in patients with perforated appendicitis with or without intra-abdominal abscess, this procedure remain useful and safe.Objective : To evaluate the postoperative outcome and complication in laparoscopic appendicectomy.Methods : This prospective observational study was conducted at Rezia Taleb Hospital, Dhaka in Bangladesh. Total 100 cases were included in this study during the period of January 2018 to December 2019. Total 100 admitted uncomplicated acute appendicitis patients who underwent LA were enrolled in this study. Diagnosis is based on patient history (symptoms) and physical examination with an elevation of neutrophilic leukocytosis and raised CRP. In this study inclusion criteria of the cases were- Age